P767 Intestinal ultrasonography predicts short term clinical remission in patients with moderate-to-severe ulcerative colitis. (30th January 2023) - Zorzi, F; De Cristofaro, E; Abreu, M T; Montesano, L; Cuccagna, E; Essofi, S; Biancone, L; Monteleone, G; Calabrese, E
Abstract: Background: Intestinal ultrasonography (IUS) is a non-invasive, easily accessible and low-cost procedure to visualize the colon and determine disease activity, extent and treatment response in IBD. Our aim was to investigate whether ultrasonographic parameters predict short-term clinical remission in ulcerative colitis (UC). Methods: Consecutive patients (pts) with moderate-to-severe UC (total Mayo score>6) starting biological therapies or small molecules were included. Patients were evaluated at baseline by clinical, biochemical, endoscopic (endoscopic Mayo score), and IUS assessments. IUS, doppler and elastographic parameters assessed at baseline before starting therapy were: bowel wall thickening (BWT), echopattern, blood flow (adapted Limberg' score), Milan Ultrasound criteria (MUC) and shear wave elastography values. The most affected colonic segment was used for all imaging assessments. Clinical remission at 3 months was defined as partial Mayo Score=0-1. Predictive factors of clinical remission at 3 months were analyzed by logistic regression. ROC curve analysis was used to identify the best cut-off of BWT in predicting clinical remission. Results: Thirty-one UC pts were enrolled (12 males [39%]; median age: 45 years, range 18-72; median disease duration: 108 months, range 3-312). Sixteen per cent of pts had left colitis and 84% had extensive UC according to the Montreal criteria. Forty-eight per cent of pts were treated with Anti-TNFs, 39% with vedolizumab, 10% with ustekinumab and 3% with tofacitinib. At baseline, 84% of patients had moderate disease and 16% severe disease according to the total Mayo score. A lower total Mayo score and partial mayo score at baseline were predictive of clinical remission at 3 months after starting biological therapy or small molecules than endoscopic Mayo score (OR 0.58, 95% CI 0.33-0.99, p=0.03; OR 0.55, 95% CI 0.29-0.99, p=0.037; OR 0.57, 95% CI 0.16-1.93, p=0.36, respectively; Figure 1, panels A-C). A lower BWT, Limberg' score and MUC at baseline were predictive of clinical remission at 3 months (OR 0.19, 95% CI 0.05-0.72, p=0.0023; OR 0.22, 95% CI 0.06-0.77, p=0.004; OR 0.48, 95% CI 0.21-0.83, p=0.001, respectively; Figure 1, panels D-F). The most accurate cut-off value of BWT for predicting clinical remission was < 6 mm with sensitivity and specificity of 70% and 82%, respectively (Figure 1, panel G). Conclusion: IUS easily predicts early clinical remission in patients with moderate-to-severe UC after therapy.